4 - Approche Marxiste et production de connaissances sur l'agriculture - Nacer BOURENANE, (Africa Development, 1984)
The agrarian issue has never been in itself a major subject of mar- xist analysis. It has often arisen while trying to understand other social fields. With MARX especially, this issue was addressed « incidentally while he was analyzing the formation and reproduction of the capitalist mode of production. The agrarian issue is given a specific position in MARX's analysis, based on the argument in his works that there appears to be a similarity between industry and agriculture regarding the developmen of the capitalist mode of production. Indeed, as far as MARX is concerned, capitalism develops both in the agricultural and the industrial sectors; it is the result of a historical process and it obeys the same historical laws. He took the agrarian theory as a mere pretext to undertake an additional in- depth study on the forms of social appropriation of part of the surplus accumulated and of the land rent. Thus, he introduced two areas of reflection and research: The first one coticerns the historical evolution of the forms of land ownership, of those of the attendant work exploitation and of the corresponding social organization. The second one concerns the various forms of capitalist develop- ment in agriciãture (tenancy, share-cropping, free land tenure, etc...), th conditions of change or of development of pre-capitalist modes of produc- tion, their fast or slow disintegration, the interest of capital in maintainin such modes of production as the peasant commodity production. On this last aspect, ENGELS contributes many elements to MARX's works, adding clear operative definitions of the major social com ponents of agriculture. He speaks in turn of landless agricultural worker of small-scale peasants, large- and medium-scale peasants, large farmers, owners of large estates. However he specifies that these are only the mos outstanding components and that there also exists « intermediary types an mixed agricultural populations». LENINE and KAUTSKY also added to the analyses of MARX and ENGELS. This was made possible because the formers' characterization of social groups was not based exclusively on economic factors. However, it should be noted that the points which are highlighted in the different analyses are conflicting for they result from an analysis in which the agraria issue is seen as an obstacle to the formalization of a system whereby capitalist mode of production is formed. This seeming contradiction prove nevertheless that an idea is making its way, that a processus of knowledge production is underway and that there is no knowledge system built aroun the agrarian question. Nacer BOURENANE, Centre de Recherches en Economie Appliquée - C.R.E.A. - Alger